2009
DOI: 10.1099/jmm.0.009910-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of bronchoalveolar lavage in evaluating new pulmonary infiltrates on computed tomography in haematology patients with fever unresponsive to broad-spectrum antibiotics

Abstract: JMM CorrespondenceRole of bronchoalveolar lavage in evaluating new pulmonary infiltrates on computed tomography in haematology patients with fever unresponsive to broad-spectrum antibiotics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
3
1
Order By: Relevance
“…We found that the quantitative BAL fluid bacterial culture yield was as low as 2.94% in patients with pneumonia who were already on antimicrobials. This yield is much lower than that of previous studies, which reported 30-80% culture rates [14-17], possibly due to use of antimicrobials before BAL. Preculture antimicrobials significantly decrease the yield of blood and sputum cultures [18-21].…”
Section: Discussioncontrasting
confidence: 66%
“…We found that the quantitative BAL fluid bacterial culture yield was as low as 2.94% in patients with pneumonia who were already on antimicrobials. This yield is much lower than that of previous studies, which reported 30-80% culture rates [14-17], possibly due to use of antimicrobials before BAL. Preculture antimicrobials significantly decrease the yield of blood and sputum cultures [18-21].…”
Section: Discussioncontrasting
confidence: 66%
“…Clearly, in severely thrombocytopenic or dyspnoeic patients, this indication may be reconsidered. Even though the use of BAL in neutropenic fever patients with chest infiltrates has been studied, it has not been reported whether the presence of this radiological sign was associated with a higher chance of isolating fungi from these BALs 26–34 …”
Section: Resultsmentioning
confidence: 99%
“…Background: Bronchoalveolar lavage is generally considered a safe procedure, even though complications like haemorrhage or aggravation of respiratory decompensation may occur in 1-2% of all patients. [26][27][28][29][30][31][32][33][34] According to the current guidelines, it should be performed in patients with neutropenic fever and lung infiltrates on their chest CT scan. 35 Clearly, in severely thrombocytopenic or dyspnoeic patients, this indication may be reconsidered.…”
Section: Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have revealed the diagnostic yield of BAL between 33-80% [27][28][29][30]. Pseudomonas was the comment organism found in the culture, and this was due to the nature of patients who underwent…”
Section: Complications During and After The Bronchoscopy Proceduresmentioning
confidence: 99%